The clinical and morphological features of ovarian Sertoli-Leydig cell tumors - E. V. Cherepanova; K. P. Laktionov; O. A. Anurova; B. O. Toloknov; A. I. Zotikov (Опухоли женской репродуктивной системы)
Ovarian Sertoli-Leydig cell tumors are rare, unusual neoplasms that generally occur in young women. There is currently no unified tactic for managing patients with this pathology. The paper presents a review of literature on clinical and morphological characteristics, prognostic factors, diagnosis, and specific features of treatment in patients with Sertoli-Leydig cell tumors.